Assessment of the colors of the melanin pigment in acral compound nevus by using a novel dermoscopy technique with surgical light illumination and saturation analysis - Sakai, Hiroshi; Tonomura, Kyoko; Shirabe, Hirotsugu; Tanaka, Masaru (Dermatology Practical & Conceptual, 2019)
IntroductionOn dermoscopy, the amount and location of melanin pigment can be assessed on the basis of its colors, ranging from black, brown to blue-gray. However, accurately recognizing a variety of melanin colors is sometimes difficult because the color of melanin pigment might change according to the character and intensity of lighting, and small melanin particles of different colors might be intermingled with each other. To resolve this issue, we developed a novel technique involving the use of surgical light illumination and saturation analysis.